Understanding the Effects of Alloy Films on the Electrochemical Behavior of Lithium Metal Anodes with Operando Optical Microscopy. Issue 10 (13th October 2021) - Sandoval, Stephanie Elizabeth; Cortes, Francisco Javier Quintero; Klein, Emily J.; Lewis, John A.; Shetty, Pralav P.; Yeh, David; McDowell, Matthew T.
Abstract : Uncontrolled morphological evolution of lithium metal anodes during cycling can lead to inactive lithium formation and excessive solid electrolyte interphase growth, causing capacity decay. Here, we investigate how interfacial alloy layers affect the growth and evolution of lithium metal during electrodeposition and stripping from stainless steel current collectors by combining electrochemical methods with operando optical microscopy. We find that thin silver films enable improved Coulombic efficiency for lithium cycling in multiple electrolyte systems compared to bare current collectors or other alloy layers. This is at least partially enabled by the observed larger lithium particle size when grown from alloys, as well as the mechanical integrity of the silver films. Operando optical microscopy reveals reduced growth of dendritic Li on silver-coated current collectors at high current densities compared to bare current collectors, as well as different dendrite growth and stripping dynamics. Together, these findings enhance our understanding of how alloy thin films can affect both the electrochemical behavior and morphological evolution of lithium metal electrodes, highlighting the benefits of interfacial engineering to enable the use lithium metal anodes in "anode-free" battery configurations.